Jazz dance a history of the roots and branches - Guarino, Lindsay; Oliver, Wendy
Unique in its focus on history rather than technique, Jazz Dance offers the only overview of trends and developments since 1960. Editors Lindsay Guarino and Wendy Oliver have assembled an array of seasoned practitioners and scholars who trace the numerous histories of jazz dance and examine various aspects of the field, including influences, training, race, aesthetics, international appeal, and its relationship to tap, rock, indie, black concert dance, and Latin dance. Featuring discussions of such dancers and choreographers as Bob Fosse and Katherine Dunham, as well as analyses of how the form's vocabulary differs from ballet, this complex and compelling history captures the very essence of jazz dance